Ultrasonic evaluation of the Jahn–Teller effect parameters. Application to ZnSe:Cr2 - Gudkov, V V; Bersuker, I B; Zhevstovskikh, I V; Korostelin, Yu V; Landman, A I (Journal of physics. Condensed matter, 2011)
A method is constructed that uses ultrasonic experiments to evaluate the parameters of the Jahn-Teller (JT) effect in impurity centers in crystals. The method is based on measurements of temperature dependent attenuation and phase velocity and does not require assumptions about mechanisms of relaxation. The results are illustrated by measurements performed on the impurity system ZnSe:Cr(2+), in which the Cr(2+) ion has a threefold degenerate T term in the ground state, subject to the [Formula: see text] JT problem. Ultrasound propagation anomalies show that the main JT distortions of the tetrahedral environment of the Cr(2+) ion are of tetragonal E type and hence the lowest branch of the adiabatic potential energy surface (APES) is formed in accordance with the [Formula: see text] problem. With dopant concentration 3.8 × 10(18) cm(-3) the modulus of the constant of linear vibronic coupling to tetragonal E type vibrations is determined by two independent experiments: |F(E)| = 5.49 × 10(-5) dyn revealed from attenuation measurements, while a slightly different value |F(E)| = 5.57 × 10(-5) dyn emerges from phase velocity measurements. Contributions of other active vibronic modes to the elastic modulus C(l) = (C(11) + C(12) + 2C(44))/2 are analyzed and it is shown that the influence of the totally symmetric mode is negligible. Using additional information about this system obtained from independent sources, we also estimated the primary force constant in the E direction (K(E)≈(1.4-4.2) × 10(4) dyn cm(-1)) and orthorhombic and trigonal saddle points of the APES in the five-dimensional space of the tetragonal and trigonal coordinates, their stabilization energies being E(JT)(O)≈81-450 cm(-1) and E(JT)(T)≈48-417 cm(-1), respectively (the variations of the K(E), E(JT)(O) and E(JT)(T) values are due to different literature data for E(JT)(E)). With these data the APES of the JT linear [Formula: see text] problem for the Cr(2+) ion in the ZnSe:Cr(2+) system is revealed.